EFECTIVENESS OF REGISTRATION OF LAND FOR THE LAND USING THE LEGAL SATISFACTION OF LAND - Imran; Syamsuddin Pasamai; Syarifuddin (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal